Penerapan Model Problem Based Learning Berbantuan Media Power Point untuk Meningkatkan Hasil Belajar PKn pada Siswa Kelas V SDN Wonokusumo VI/45 - Widji Astuti; Siti Arifah; Sri Setik Nurhamami (Journal on Education, 2023)
This study aims to determine the increase in Civics learning outcomes through the problem-based learning model assisted by power point media. The research subjects were fifth grade students at SDN Wonokusumo VI/45 for the academic year 2022/2023, with a total of 32 students consisting of 16 female students and 16 male students. This research was conducted in 2 cycles, each cycle consisting of two meetings with one meeting for the implementation of learning and one meeting for the end of the cycle test. The design in each of these cycles consists of four stages, namely starting with planning, then taking action, observing, and finally reflecting. Research data on student civics learning outcomes were collected using the usual multiple choice objective test method with four options. Data were analyzed using quantitative descriptive statistics. The results showed an increase in PPKn learning outcomes for fifth grade students. This can be seen from the average in cycle I, which increased from 62.25 to 84 in cycle II. Thus it can be concluded that the problem based learning model assisted by power point media can improve the learning outcomes of fifth grade students at SDN Wonokusumo VI/45.